Photoinduced C(sp3)–H sulfination empowers the direct and chemoselective introduction of the sulfonyl group. Issue 41 (6th October 2021) - Jin, Shengfei; Haug, Graham C.; Trevino, Ramon; Nguyen, Viet D.; Arman, Hadi D.; Larionov, Oleg V.
Abstract : The photoinduced C–H sulfination of abundant aliphatic C–H bonds provides direct access to all major classes of organosulfur compounds via the intermediacy of synthetically versatile sulfinate salts. Abstract : Direct installation of the sulfinate group by the functionalization of unreactive aliphatic C–H bonds can provide access to most classes of organosulfur compounds, because of the central position of sulfinates as sulfonyl group linchpins. Despite the importance of the sulfonyl group in synthesis, medicine, and materials science, a direct C(sp 3 )–H sulfination reaction that can convert abundant aliphatic C–H bonds to sulfinates has remained elusive, due to the reactivity of sulfinates that are incompatible with typical oxidation-driven C–H functionalization approaches. We report herein a photoinduced C(sp 3 )–H sulfination reaction that is mediated by sodium metabisulfite and enables access to a variety of sulfinates. The reaction proceeds with high chemoselectivity and moderate to good regioselectivity, affording only monosulfination products and can be used for a solvent-controlled regiodivergent distal C(sp 3 )–H functionalization.